SELF DECLARE DALAM PROSES PENETAPAN SERTIFIKASI HALAL - Nahdhah Nahdhah; Iwan Riswandie (Al-Adl : Jurnal Hukum, 2026)
This study aims to examine and analyze the regulatory framework of the self-declaration mechanism in the halal certification process and the adequacy of the normative basis for oversight by the Halal Product Assurance Organizing Agency (BPJPH) under Law Number 33 of 2014 concerning Halal Product Assurance. The research is prompted by several controversies, such as the "Nabidz halal wine" case, in which products obtained halal certification through the self-declaration mechanism, subsequently triggering significant public debate. These cases demonstrate a multiplicity of interpretations regarding the oversight mechanisms within the self-declaration-based certification system. Employing a normative legal research methodology, this study analyzes Articles 49 and 50 of Law Number 33 of 2014. The findings reveal that while the self-declaration mechanism legally expands the reach of halal certification, the presence of vague clauses results in a lack of legal certainty regarding product halal status. Furthermore, the normative foundation for BPJPH oversight is legally insufficient; although Articles 49 and 50 grant supervisory authority, they are characterized as open norms and do not explicitly encompass the self-declaration mechanism.